PENGARUH PENGGUNAAN EKSTRAK BUAH JERUK NIPIS (CITRUS AURANTIFOLIA) SEBAGAI KOAGULAN DALAM PEMBUATAN TAHU SUSU TERHADAP KADAR PROTEIN, DERAJAD KEASAMAN DAN MUTU ORGANOLEPTIK - Anastasia Wali (Jurnal Sains Peternakan, 2013)
The purpose of this study was to determine the effect of the use of lemon fruit extract ( Citrus aurantifolia ) as a coagulant in the manufacture know the protein content of milk , the degree of acidity and the quality organoleptik.Hasil Research shows that the use of lemon extract to the addition of 30 ml can be very real effect the protein content of the milk out and have the highest protein yield is 23.52 % , and the addition of 20 ml of the protein content of 22.96 % and 10 ml of the protein content of 17.79 % and the texture of lemon extract 10 ml with a value of 3 , 5 , with a value of 20 ml and 30 ml of 2.7 with a value of 2.1 . The results showed that there is a significant influence ( P < 0.01 ) the protein content of milk and know there is a real effect P < 0.05 in the texture of the curd , and there is no significant influence on the degree of acidity , color , flavor and aroma out of milk . In addition of lemon extract the highest protein content at the level of 30 cc of the number of protein content 23.99 % , so in this study the higher level of lemon extract , the higher the protein content produced . In the know also affect the texture of the real and the average value of the highest preference level at level 10 .Keywords : fresh milk , lemon extract , milk , coagulant , protein , pH , Appearance